SELF-ASSESSMENT ISSUES IN THE CONTEXT OF THE ORGANIZATION INDEPENDENT LEARNING ACTIVITIES OF STUDENTS HIGHER PEDAGOGICAL EDUCATIONAL INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2008)
The article reveals the role and influence of self-evaluation in the process of organizing and realizing self directed learning activities by students of higher teacher training institutions.